ĐẶC ĐIỂM SINH HỌC CỦA MỘT SỐ LOÀI NẤM HỌ BOLETACEAE TẠI KHU BẢO TỒN THIÊN NHIÊN KON CHƯ RĂNG, TỈNH GIA LAI - Phạm, Thị Hà Giang; O.V., Morozova; Phạm, Mai Phương; Vũ, Đình Duy; Dương, Văn Tăng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
In this publication, we describe in detail 3 species of Boletaceae family mushrooms recorded in Kon Chu Rang Nature Reserve and described for the first time from samples in Vietnam. Of these, the species Tylopilus subotsuensis is new to science described in our final paper of 2020; The remaining 2 samples have only been identified at the genus level and they may be new species to science (Chalciporus sp., Phylloporus sp.). The nucleotide sequences obtained during the study were deposited in GenBank.